Free stream flow and forced convection heat transfer around a rotating circular cylinder subjected to a single gust impulse. (August 2016) - Ikhtiar, Usman; Manzoor, S.; Sheikh, N.A.; Ali, Muzaffar
Highlights: The flow physics and the heat transfer characteristics are more sensitive to the upstream gust at higher rotation rates i.e. the second vortex shedding regime, throughout the Reynolds number range. Moreover, the temperature profiles and the Strouhal number recorded in the present work show maximum variation in the second vortex shedding regime. The upstream gust causes the average Nusselt number to increase in the first and the second vortex shedding regimes but interestingly, the pattern is reversed in the intermediate vortex suppression region. Abstract: The effect of a single gust impulse on free stream flow and forced convection heat transfer across a two dimensional steadily rotating circular cylinder is numerically investigated. Reynolds number is varied between 80 and 160 while the non-dimensional steady rotation rate is restricted to a maximum value of 5 for a fluid with constant Prandtl number of 7. The governing equations namely continuity, momentum and energy equations have been solved using the Constant Wall Temperature boundary condition. Interesting results are presented depicting the behavior of the stretched boundary layer and the temperature field around the rotating cylinder. The convective heat transfer is observed to evolve differently for different combinations of the aforementioned parameters under the influence of the upstream gust.